Communication Between Cardiomyocytes and Fibroblasts During Cardiac Ischemia/Reperfusion and Remodeling: Roles of TGF-β, CTGF, the Renin Angiotensin Axis, and Non-coding RNA Molecules - Flores-Vergara, Raúl; Olmedo, Ivonne; Aránguiz, Pablo; Riquelme, Jaime Andrés; Vivar, Raúl; Pedrozo, Zully (Frontiers in Physiology, 2021)
Crosstalk between cells is one of the hallmarks to understand the physiology and pathology of biological systems. Paracrine/autocrine signaling, direct cell-to-cell interplay and interactions through extracellular matrix are three different types of cell communication that regulate the response to different stimuli. In the heart, cardiomyocytes, fibroblasts and endothelial cells interact to form the cardiac tissue and according to the type or concentration of humoral factors released during cardiac pathologies -such as myocardial infarction- tissue damage or protection may be induced. On the other hand, cardiac remodeling is also regulated by humoral factors released by cardiomyocytes and fibroblast to regulate the function of each other. Knowledge of the released molecules and cellular signal pathways are crucial to find an appropriate tissue-preserving treatment during or after reperfusion. Different therapies have been developed to protect cardiac tissue from reperfusion-induced injury. Abundant pre-clinical research has been performed in order to find promising drugs or maneuvers to inhibit cardiac damage, but despite great success in animal models, it has not been possible to completely translate these cardioprotective effects in humans. In this review, we developed an updated search of the principal molecules, pathways and mechanisms through cardiomyocytes and cardiac fibroblast crosstalk during ischemia/reperfusion injury. We also discuss molecules studied in pre-clinical settings for the treatment of myocardial infarction, while providing a clinical perspective of these potential therapeutic agents.